Urgensi Media Pembelajaran Pada Pembelajaran Matematika Ditinjau Dari Minat Siswa Belajar Matematika / The Urgency of Learning Media in Mathematics Learning in View of Students' Interest in Learning Mathematics - Fatikh Inayahtur Rahma; Eddy Sutadji; Aynin Aynin (Al-Mudarris: Journal Of Education, 2023)
Abstract and systematic characteristics make mathematics a difficult subject for students. Appropriate learning methods can affect students' interest in mathematics. Such as using media. The use of media in learning mathematics can contribute positively and provide maximum results in increasing students' understanding of the material being taught. The purpose of this study is to determine students' interest in mathematics and the importance of media in learning mathematics. Learning mathematics can be said to be effective if there is an increase in student learning outcomes, namely the ability to solve mathematical problems, are skilled, creative, and are active in the learning process. This research uses qualitative research. Data collection techniques used questionnaires, interviews, and documentation which were carried out at SDI KHA Wahid Hasyim Bangil. The data obtained was that teacher used media in learning mathematics and students have an interested in learning mathematics by 96.30%. This shows that the media has a role in the learning process, especially mathematics.